Direct Formation of Sub-Micron and Nanoparticles of a Bioinspired Coordination Polymer Based on Copper with Adenine - Vegas, Verónica G. (Polymers (Basel), 2017)
We report on the use of different reaction conditions, e.g., temperature, time, and/or concentration of reactants, to gain control over the particle formation of a bioinspired coordination polymer based on copper(II) and adenine, allowing homogeneous particle production from micro- to submicro-, and up to nano-size. Additionally, studies on this reaction carried out in the presence of different surfactants gives rise to the control of the particle size due to the modulation of the electrostatic interactions. Stability of the water suspensions obtained within the time and pH has been evaluated. We have also studied that there is no significant effect of the size reduction in the magnetic properties of the Cu(II)-adenine coordination polymer.